Burden of Children Hospitalized With Pertussis in Canada in the Acellular Pertussis Vaccine Era, 1999–2015. (8th December 2018) - Abu-Raya, Bahaa; Bettinger, Julie A; Vanderkooi, Otto G; Vaudry, Wendy; Halperin, Scott A; Sadarangani, Manish; ,
Abstract: Background: Recent increases in pertussis morbidity and mortality rates among young infants have led to a recommendation in some countries for vaccination against pertussis during pregnancy. Having data on the burden of pediatric pertussis in a large population over time is important for establishing the true burden of disease in the acellular pertussis (aP) vaccine era. Here, we describe age-specific epidemiology and morbidity and mortality rates in children hospitalized with pertussis over 17 years across Canada in the aP vaccine era. Methods: Patients aged ≤16 years who were admitted to 1 of 12 pediatric tertiary-care hospitals across Canada between 1999 and 2015 with confirmed (laboratory-confirmed or epidemiologically linked) or probable (clinically diagnosed) pertussis were included. Results: Overall, 1402 patients with pertussis were included. Infants aged <2 months had the highest mean annual incidences of pertussis hospitalization and intensive care unit (ICU) admission (116.40 [95% confidence interval (CI), 85.32–147.49] and 33.48 [95% CI, 26.35–40.62] per 100 000 population, respectively). The overall proportion of children who required ICU admission was 25.46%, and the proportion was highest in infants aged <2 months (37.90%). Over the span of this study, 21 deaths occurred. Age of <16 weeks, prematurity, encephalopathy, and a confirmed pertussis diagnosis were independent risk factors for ICU admission. Age of <4 weeks, prematurity, and female sex were independent risk factors for death. Conclusions: In the aP vaccine era, endemic pertussis still contributes considerably to childhood morbidity and death, particularly in infants aged <2 months. Vaccination against pertussis during pregnancy has the potential to reduce this disease burden. Abstract : Infants aged <2 months remain the major contributor to pediatric pertussis hospitalization. Independent risk factors for intensive care unit admission were age of <16 weeks, prematurity, encephalopathy, and confirmed pertussis diagnosis. Independent risk factors for death were age of <4 weeks, prematurity, and female sex.